Camera Traps Document Infant Corpse Carrying Behaviour in Multiple Unhabituated Chimpanzee Populations - Elena Bersacola; Matthew R. McLennan; Joana H. Bessa; Henry Camara; Maimuna Jaló; Vicent Kiiza; Gnan Mamy; Nicholas Mpanga; Vicky Oelze; Marina Ramon; Américo N. W. Sanhá; Laura vanHolstein; et al. (Ecology and Evolution, 2025)
ABSTRACT Camera traps are an important tool for wildlife research, particularly for estimating species distribution and habitat use. Although they are increasingly used to study animal behaviour, such as tool use and foraging, there are fewer examples of their use in detecting rare behaviours that cannot be predicted in terms of where and when they may occur. Comparative thanatology, the study of non‐human animal responses to death, has demonstrated that examining behaviours such as infant corpse carrying (ICC) can offer valuable insights into animal cognition, including maternal bonds, grief, and levels of death awareness. Here, we investigate the efficacy of camera traps in capturing ICC in four unhabituated chimpanzee (Pan troglodytes) populations across West and East Africa, involving a total of 18 chimpanzee communities. We compare ICC detection rates and associated demographic and behavioural data derived from camera traps to published cases recorded through direct observations of habituated communities, the only previous source of ICC reports in wild chimpanzees. Camera traps recorded ICC in seven communities at an average rate of 0.46 cases/year, 2.3 times higher than the 0.20 cases/year recorded through direct observations in 10 habituated communities. The carrying duration in the 10 ICC cases recorded by camera traps ranged from a day or less to at least 28 days (median = 7 days). All 10 ICC cases involved deceased infants with an estimated age bracket between 0 and 0.5 and 2 and 3 years (median: 1 and 1.5 years), and eight out of 10 cases involved a single adult female carrier. Associated demographic and behavioural data support predictions around mother–infant bonds, post‐parturient conditions, and death awareness hypotheses. We conclude that ICC is more common than previously reported in chimpanzees and that camera traps can effectively capture infrequent behaviours such as ICC, making them a promising non‐invasive tool for studying animal behaviour across large spatial scales.